Constitutional Imperatives: Examining the Urgency of Term Limits for Members of the House of Representatives - Baharuddin Riqiey; Syofyan Hadi (Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2024)
UUD NRI 1945 is the highest law in Indonesia's hierarchy of rules and regulations. One of the principles adopted by the UUD NRI 1945 is the principle of constitutionalism. Proof that the UUD NRI 1945 adheres to the principle of constitutionalism can be proven by the existence of Article 7, Article 23E, Article 24A, Article 24B, and Article 24C of the UUD NRI 1945. Meanwhile, the DPR, one of the state institutions mentioned in Chapter VII of the UUD NRI 1945, does not regulate term limits. This research explains the urgency of regulating term limits for DPR members from a constitutionalism perspective. This research is normative legal research using a statutory, conceptual, case, and comparative approach. The results of this research show that the absence of regulations regarding term limits for members of The House of Representative in the UUD NRI 1945 is not in accordance with the principles of constitutionalism adopted by the UUD NRI 1945. The urgency of limiting the terms for members the House of Representative is to: (1) uphold the principles of constitutionalism, (2) prevent arbitrary actions, (3) realize legal certainty, (4) improve the implementation of democracy in Indonesia, (5) prevent authoritarianism, and (6) Carrying out regeneration.